3D culture of cancer cells in alginate hydrogel beads as an effective technique for emergency cell storage and transportation in the pandemic era - Alallam, Batoul; Oo, May Kyaw; Ibrahim, Wisam Nabeel; Doolaanea, Abd Almonem (Wiley, 2021)
Due to the restrictions in accessing research laboratories and the challenges in providing proper storage and transportation of cells during the COVID-19 pandemic, having an effective and feasible mean to solve these challenges would be of immense help. Therefore, we developed a 3D culture setting of cancer cells using alginate beads and tested its effectiveness in different storage and transportation conditions. The viability and proliferation of cancer cells were assessed using trypan blue staining and quantitative CCK-8 kit, respectively. The developed beads allowed cancer cells survival up to 4 weeks with less frequent maintenance measures such as change of the culture media or subculture of cells. In addition, the recovery of cancer cells and proliferation pattern were significantly faster with better outcomes in the developed 3D alginate beads compared to the standard cryopreservation of cells or the 2D culture conditions. The 3D alginate beads also supported the viability of cells while the shipment at room temperature for a duration of up to 5 days with no humidity or CO2 support. Therefore, 3D culture in alginate beads can be used to store or ship biological cells with ease at room temperature with minimal preparations.